Global, regional and national incidence, mortality and disability‐adjusted life‐years of skin cancers and trend analysis from 1990 to 2019: An analysis of the Global Burden of Disease Study 2019 - Zhang, Wei (Cancer Med, 2021)
BACKGROUND: Information about global and local epidemiology and trends of skin cancers is limited, which increases the difficulty of cutaneous cancer control. METHODS: To estimate the global spatial patterns and temporal trends of skin cancer burden. Based on the GBD 2019, we collected and analyzed numbers and age‐standardized rates (ASR) of skin cancer incidence, disability‐adjusted life years (DALYs) and mortality (ASIR, ASDR, and ASMR) in 204 countries from 1990 through 2019 were estimated by age, sex, subtype (malignant skin melanoma [MSM], squamous‐cell carcinoma [SCC], and basal‐cell carcinoma [BCC]), Socio‐demographic Index (SDI), region, and country. Temporal trends in ASR were also analyzed using estimated annual percentage change. RESULTS: Globally, in 2019, there were 4.0 million BCC, 2.4 million SCC, and 0.3 million MSM. There were approximately 62.8 thousand deaths and 1.7 million DALYs due to MSM, and 56.1 thousand deaths and 1.2 million DALYs were attributed to SCC, respectively. The men had higher ASR of skin cancer burden than women. The age‐specific rates of global skin cancer burden were higher in the older adults, increasing trends observed from 55 years old. Geographically, the numbers and ASR of skin cancers varied greatly across countries, with the largest burden of ASIR in high SDI regions. However, an unexpected increase was observed in some regions from 1990 to 2019, such as East Asia, and Sub‐Saharan Africa. Although there was a slight decrease of the ASMR and ASDR, the global ASIR of MSM dramatically increased, 1990–2019. Also, there was a remarkable increase in ASR of BCC and SCC burden. CONCLUSIONS: Skin cancer remains a major global public health threat. Reducing morbidity and mortality strategies such as primary and secondary prevention should be reconsidered, especially in the most prevalent and unexpected increased regions, especially for those areas with the greatest proportions of their population over age 55.